Prosedur Penyusunan Rencana Anggaran Biaya Lumpsum pada Satuan Pengawasan Intern - Maulina Alfindy; Anik Yuliati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research discusses the procedure for preparing a lumpsum Budget Plan (RAB) at the Internal Audit Unit. The goal of the study is to describe and examine the systematic steps in preparing an effective and efficient RAB lumpsum for internal supervision activities. Descriptive qualitative research methodology is employed, and data is gathered through in-depth interviews, literature reviews, and observation. The research also identified factors to consider in preparing the RAB lumpsum, such as the complexity of the supervision activities, duration, location, and applicable regulations. The research conclusion emphasizes the importance of careful planning and coordination between related units to produce an accurate and accountable RAB lumpsum.